Implementation of Principles Good Corporate Governance (GCG) Procurement of Goods and Services by the Regional Public Service Agency at The Jatisari Regional Public Hospital, Karawang - Asep Sunandar; Erliany Syaodih; Nining Handayani (Research of Service Administration Health and Sains Healthys, 2026)
This study examines the implementation of Good Corporate Governance (GCG) principles in the procurement of goods and services at Jatisari Regional Public Hospital, Karawang, which operates as a Regional Public Service Agency (BLUD). A qualitative descriptive method with a phenomenological approach was employed to analyze the application of transparency, accountability, responsibility, independence, and fairness in procurement processes. Data were collected through in-depth interviews with hospital directors, procurement officers, and patients, supported by direct observation and document analysis. The findings indicate that Jatisari Regional Public Hospital has made positive progress in implementing GCG principles through the use of electronic procurement systems, public information disclosure, and compliance with regulatory standards. Nevertheless, several challenges remain, including incomplete digitalization, inconsistent reporting mechanisms, political and bureaucratic intervention affecting institutional independence, limited human resource capacity, and unequal distribution of facilities across service units. The study concludes that while GCG implementation demonstrates a positive trajectory, substantial improvements are required in system strengthening, human resource development, and the enhancement of information technology–based governance.